2017
DOI: 10.5539/jas.v9n3p117
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Arbuscular Mycorrhizal Fungi of Durum Wheat (Triticum durum Desf.) Fields of the East of Algeria

Abstract: In Algeria, in the semi-arid and arid areas cereal production is limited because of many constraints like lack of mineral elements (phosphorus and nitrogen), low organic matter and an insufficient water reserve due to the low rainfall. Most researches on durum wheat (Triticum durum Desf.) are undertaken to increase its productivity. In recent years several methods have been used including using microorganisms. Arbuscular Mycorrhizal fungi (AMF) appear to have important roles in plants in various soil condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…In another study under similar conditions in acidic soils, Castillo et al ( 2016b ) described 26 fungal species with a prevalence of Acaulospora and Claroideoglomus . This dominance of Acaulospora spores in soils cropped with wheat was also observed by Hu et al ( 2015 ) in North China and by Nadji et al ( 2017 ) in Algeria, however in the last study Glomeraceae species was also detected as highly abundant.…”
Section: Am Functional Diversitysupporting
confidence: 80%
“…In another study under similar conditions in acidic soils, Castillo et al ( 2016b ) described 26 fungal species with a prevalence of Acaulospora and Claroideoglomus . This dominance of Acaulospora spores in soils cropped with wheat was also observed by Hu et al ( 2015 ) in North China and by Nadji et al ( 2017 ) in Algeria, however in the last study Glomeraceae species was also detected as highly abundant.…”
Section: Am Functional Diversitysupporting
confidence: 80%
“…There are various evidences in relation to the fact that tillage disturbs soils and decelerates their biological processes such as the decrease of mycorrhization rates under CT compared to NT [5]. Moreover, MR variability among cultivation year could be explained by climate effect on the establishment of this symbiosis [30].…”
Section: Mycorrhization Ratementioning
confidence: 99%
“…Van Groenigen et al (2010) have shown, using both ergosterol and PLFA analyses, that while reduced tillage increased biomass of saprotrophic fungi in the 0-5 cm soil layer, it increased AMF biomass across the whole plough layer. The aridity of the study area (a rainfall close to 400 mm) may explain the dominance of the AMF biomass (Rodriguez et al, 2004;Duponnois et al, 2012;Nadji et al, 2017). Similarly, some characteristics of the study area soil such as the low total phosphorus level (Nadji et al, 2017) and the alkaline soil pH in relation with limestone mother rock (Djebaili et al, 1984;Halitim et al, 1988) also contributes to the AMF installation.…”
Section: Discussionmentioning
confidence: 90%
“…The aridity of the study area (a rainfall close to 400 mm) may explain the dominance of the AMF biomass (Rodriguez et al, 2004;Duponnois et al, 2012;Nadji et al, 2017). Similarly, some characteristics of the study area soil such as the low total phosphorus level (Nadji et al, 2017) and the alkaline soil pH in relation with limestone mother rock (Djebaili et al, 1984;Halitim et al, 1988) also contributes to the AMF installation. Coutinho et al (2015) reported that low levels of phosphorus allow production by AMF of a large number of propagules in an environment with few nutrients.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation